(untitled) (International Journal of Banking and Finance, 2025)
This study explores the impact of economic policy uncertainty on herd behaviour in the Chinese stock market. As economic policy uncertainty increases, market information becomes highly chaotic and complex, making reliable information scarce and challenging for investors to make independent decisions. Particularly in the Chinese stock market, where retail investors dominate and generally lack professional financial knowledge and deep market analysis skills, these investors are more likely to mimic the behaviours of other market participants. Using monthly data from January 2011 to December 2023, and employing panel regression for empirical analysis, this research aims to explore the specific effects and mechanisms of economic policy uncertainty on herd behaviour, addressing a gap in the existing literature regarding how economic policy uncertainty directly influences investor behaviour in terms of manner and extent. The study’s findings indicate that economic policy uncertainty has a significant and varied impact on herding behaviour across different market segments. Specifically, economic policy uncertainty significantly promotes herding behaviour in the Science and Technology Innovation Board, while it inhibits herding behaviour in the Main Board. Economic policy uncertainty also inhibits herding behaviour in the ChiNext, but not as significantly as in the Main Board. This diversity in impact highlights the complex nature of economic policy uncertainty’s influence on herd behaviour.